Microorganism Profiles of Penile Prosthesis Removed for Infection, Erosion, and Mechanical Malfunction Based on Next-Generation Sequencing. Issue 2 (26th December 2021) - Chung, Paul H.; Leong, Joon Yau; Phillips, Caleb D.; Henry, Gerard D.
ABSTRACT: Background: Next-generation sequencing (NGS) is an emerging technology that may allow for more sensitive and sophisticated microbial testing of the microbiota of penile prostheses (PP). Aim: To describe the microorganism profiles of PP explanted for infection, erosion, and mechanical malfunction using NGS. Methods: All patients who underwent PP removal by two physicians at two institutions were identified. Differences in alpha diversity (ie, number of species detected, species diversity across samples) and microbiome compositional profiles (Bray-Curtis community dissimilarities) across samples were assessed using ANOVA and PERMANOVA, respectively. Outcomes: Number of species detected, species diversity across samples, and microbiome compositional profiles. Results: A total of 83 patients who underwent device removal for infection (n = 8, 10%), erosion (n = 5, 6%), and mechanical malfunction (n = 70, 84%) were included. When considering all devices, 56% (n = 48) of NGS and 29% (n = 24) of standard cultures resulted positive for presence of microorganisms. Culture only detected the most abundant NGS species in 62.5% (n = 5) of infected devices. Species richness and microbiome compositional profiles varied by surgical indication, but not by age, race, diabetes status, or implant duration. Most frequent organisms by surgical indication were Pseudomonas aeruginosa (infection), Staphylococcus epidermidis (erosion), and Escherichia coli (mechanical malfunction). The highest relative abundance organisms were P aeruginosa (infection), Corynebacterium jeikeium (erosion), and E coli (mechanical malfunction). Clinical Implications: Identifying microbiome profiles of PP removed for infection, erosion, and mechanical malfunction may guide the selection of peri-operative antibiotics and PP antibiotic coatings or hydrophilic dip solutions for each individual scenario. Strengths and Limitations: While this is the first study to utilize next-generation sequencing to evaluate penile prosthesis biofilm, the clinical significance of these findings has yet to be determined. A prospective, randomized trial aimed at evaluating the clinical significance of NGS in patients with PP infection is currently underway. Conclusion: NGS testing identified distinct microbiome profiles of PP removed for infection, erosion, and mechanical malfunction.